Fluvial facies architecture and provenance history of the Abrahamskraal-Teekloof formation transition (lower Beaufort group) in the main Karoo Basin - Paiva, Francisco (Department of Geological Sciences, 2016)
The Middle Permian lower Beaufort Group in the southern main Karoo Basin comprises of the fluvio-lacustrine Abrahamskraal and the overlying Teekloof and correlative Middleton Formations. These units are mainly made up of mudrocks with subordinate fine-grained sandstone-rich intervals. The objective of this mainly qualitative facies analysis study is the evaluation of the vertical and lateral abundances of the facies associations in order to decouple the preserved tectonic and climatic signals in the formations. The results on the stratigraphic trends should aid paleo-environmental, paleontological, and basin analysis studies, and improve our understanding of reservoir dynamics (e.g., permeability, connectivity) when used as outcrop analogues for subsurface fluvial reservoirs. High resolution facies mapping showed that flat-topped, laterally continuous (for 10s of Kms) channel-belt complexes are the most common external architecture of the channel sandstones in all formations.